Evaluation of Freezing-Induced Changes in Aroma Profiles of Pomegranate Juice by Quantitative Descriptive Sensory Analysis, Gas Chromatography–Mass Spectrometry/Olfactometry, Odor Activity Values, Orthogonal Partial Least Squares–Discriminant Analysis, and Odorant Addition Experiment - Yixiu Chen; Peng Wang; Wanying He; Honglei Tian; Jingzhang Geng; Runguang Zhang; Ping Zhan (Foods)
Freezing is employed to preserve the quality of pomegranate juice (PJ) for producing nutritious ready-to-drink beverages. However, the aroma compounds of PJ undergo significant alterations post-freezing. This study aimed to examine the impacts of different freezing temperatures (−20 °C, −40 °C, and −80 °C) on the flavor profiles of PJ, using fresh PJ as a control. The quantitative descriptive sensory analysis (QDA) results showed that grassy, woody, and fruity attributes of PJ were notably diminished following the freezing treatment. In total, 34 volatiles were identified by gas chromatography–mass spectrometry (GC-MS), of which 14 were perceived by GC–olfactometry (GC-O). Together with orthogonal partial least squares–discriminant analysis (OPLS-DA) and OAV tests, five volatiles were determined as key differential markers, and three (hexanol, (Z)-3-hexen-1-ol and β-myrcene) were selected for further odorant addition experiments. The results verified that (Z)-3-hexen-1-ol was the primary odorant for enhancing the grassy and fruity notes of PJ, while hexanol and β-myrcene were crucial for enhancing grassy and woody attributes, respectively.